AUGMENTED REALITY IN PHYSICS LESSONS: EXPERIENCE USING PHYSICS LAB AR IN BLENDED LEARNING - Slobodianyk, Olha (Physical and Mathematical Education, 2025)
Formulation of the problem. Changes in the world of technology, particularly in the fields of augmented and virtual reality, breakthroughs in artificial intelligence, and the transition to blended learning, are forcing educational institutions to adapt their methods and approaches to the educational process. Recent studies have demonstrated that the application of augmented reality (AR) in education presents numerous advantages that positively influence the educational process.Materials and methods. A set of methods was employed, including analysis, systematization, and synthesis of scholarly sources; a review of scientific publications by both domestic and international researchers; examination of regulatory and policy documents; and reflection on our own professional experience. In particular, a student survey was conducted regarding the application of AR technologies in the educational process, complemented by an analysis of learners’ academic performance before and after the implementation of the study.Results. Blended learning is a modern pedagogical model that combines classroom teaching with digital technologies, allowing students to study material independently at a time convenient for them. This form of learning facilitates the integration of traditional methods with interactive tools, making the educational process more flexible and allowing students to work at their own pace, thereby increasing their level of independence. For natural science and mathematics subjects, conducting experiments is a key aspect of learning. In blended learning, this is made possible by augmented reality technologies and interactive simulations, particularly for students who are unable to attend face-to-face classes due to various reasons.Conclusions. The integration of AR into education fosters interactivity, increases learner motivation, and stimulates interest in the learning process. Visualization tools enhance comprehension of complex phenomena, while personalized pathways allow students to work at a pace aligned with their individual needs. Nevertheless, it must be acknowledged that modern students often display a strong dependency on digital devices. To mitigate potential negative impacts on the development of essential soft skills and social competencies, the use of AR and VR should be carefully balanced and applied in moderation.
Keywords: augmented reality; blended learning; physics; educational process